Influential factors shaping Vietnamese students' intentions to reduce the use of single-use plastics - Thi Thanh Thuy Phan; Tai Thi Nhat Phan; Hong Thi Thu Nguyen (Sustainable Futures)
Abstracts: Environmental degradation due to the overwhelming of plastic waste has raised concerns at an alarming rate worldwide. To ensure a sustainable future and fulfill the Sustainable Development Goals (SDGs) with particular emphasis on plastic waste and pollution (SDG 11, 12, and 14), understanding the factors that affecting university students’ beliefs and perspectives towards pro-environmental behaviour are crucial, assisting relevant stakeholders to develop effective environmental initiatives that drive behavioural change. This research seeks to uncover the main factors driving students' intention to reduce the use of single-use plastics (SUPs) in Danang City, Vietnam, by utilizing the extended theory of reasoned action as a theoretical framework. The results analyzed from 429 valid data show that environmental attitude, subjective norm and legal and regulatory measures have significant impacts on the intention to reduce the use of SUPs among higher education students, with legislative factor having the strongest weight. The findings also reveals that significant differences are shown in gender and study background (educational level and pedagogical training status) towards SUPs reduction intention. These findings offer new insights and comprehensive information for not only policy-makers in assessing environmental interventions and designing effective programs tailored to specific group needs but also for academics in conducting studies focused on plastic reduction behaviour.